(untitled) (International Journal of Food and Nutritional Sciences, 2022)
PMMY is a scheme designed by the GOI to provide financial assistance to the weaker section of the society. The main objective of this research endeavour is to evaluate the performance of PMMY from FY 2015-16 to FY 2021-22. The scheme was designed for the weaker section that directly cannot access the banking facilities, MUDRA provide all sought of financial assistance. The economy has faced a largest financial jerk during covid19, the paper will try to highlight the effectiveness of the scheme before and after the covid19 recovery and its contributions as financial support in handholding, capacity building and support to micro enterprise.